Bees in the six: Determinants of bumblebee habitat quality in urban landscapes. Issue 3 (21st March 2022) - Conflitti, Ida M.; Arshad Imrit, Mohammad; Morrison, Bandele; Sharma, Sapna; Colla, Sheila R.; Zayed, Amro
Abstract: With growing urbanization, it is becoming increasingly important to design cities in a manner that sustains and enhances biodiversity and ecosystem services. Native bees are critical pollinators that have experienced substantive declines over the past several decades. These declines have captured the attention of the public, particularly urbanites, prompting a large interest in protecting pollinators and their habitats in cities across North America and Europe. Unfortunately, we currently lack research about specific features of urban environments that can enhance the fitness of pollinators. We carried out an intensive study of Bombus impatiens, the Common Eastern Bumblebee, in the city of Toronto (Canada's largest city), to better understand landscape parameters that provide high‐quality habitat for this species and likely other generalist bees. We divided the city into 270 grid cells and sampled a large number of worker bees, which were then genotyped at twelve hypervariable microsatellite loci. The genetic data allowed us to quantify the effective number of colonies and foraging distance for bumblebees in our study area. We then asked how the city's landscape and human population demography and income are associated with the availability of high‐quality habitat for B . impatiens . Several aspects of Toronto's landscape influenced colony density and foraging range. Urbanization had a clear effect on both colony density and foraging distance of workers. On the other hand, functional (i.e., not cosmetic) green space was often associated with higher quality habitats for bumblebees. Our study suggests several planning strategies to enhance habitat quality for bumblebees and other pollinators in cities. Abstract : Population genetic analysis of several hundred bumblebees in the city of Toronto indicated that urbanization and the availability of functional (i.e., not cosmetic) green space influenced habitat quality for the common Eastern Bumblebee and likely other generalist pollinators. Our study suggests several planning strategies to enhance habitat quality for bumblebees and other pollinators in cities.